Spray characteristics of gasoline/PODE and diesel/PODE blends in a constant volume chamber. (August 2019) - Liu, Jialin; Feng, Lei; Wang, Hu; Zheng, Zunqing; Chen, Beiling; Zhang, Diping; Yao, Mingfa
Highlights: Spray characteristics of gasoline/PODE and diesel/PODE are studied in CVC. PODE has longer spray tip penetration compared to gasoline and diesel ( Ta  = 300 K). PODE shows smaller spray cone angle than diesel under evaporating condition. Lower equivalence ratio along both directions can be obtained by fueling PODE. Abstract: Polyoxymethylene dimethyl ethers (PODE) is an emerging alternative fuel, which has been extensively investigated and shows great potential to improve the combustion performance in both conventional diesel engine and novel combustion modes. In this paper, the spray characteristics of gasoline/PODE and diesel/PODE blends under different injection pressures and ambient pressures were investigated in a constant volume chamber under both non-evaporating and evaporating conditions. Experimental results show that under evaporating condition, the spray tip penetration of PODE is higher than gasoline, but shorter than diesel due to different volatility, along with smaller spray cone angle compared to diesel, and reduced spray cone angle can be obtained with higher injection pressure. Under non-evaporating condition, longer spray tip penetration and larger spray cone angle are observed with PODE. PODE is beneficial to reduce the equivalence ratio along the axial and radical directions for both gasoline and diesel due to its high oxygen content. In the meanwhile, PODE has larger SMD compared to gasoline, and smaller SMD for gasoline, diesel and PODE can be obtained by increasing injection pressure and lowering the ambient pressure. At last, the experiment data provided in this paper will also contribute to the spray model calibration.